The Role of Mobile Assisted Language Learning in Improving the Pronunciation of Students of English in the College of Education for Women at Al-Iraqia University (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research tackles the effect of mobile assisted language learning (henceforth, MALL) in improving the students’ pronunciation of English language, in particular the pronunciation of word stress. It aims at:• Identifying the term MALL, its uses, advantages, and disadvantages.• Exploring the effectiveness of MALL devices both as instructional tools and learning resources within and beyond classroom learning environments to develop language skills, particularly pronunciation of word stress.The experimental design is pretest_experiment_post_test. To conduct the study, the researcher made a test on the pronunciation of word stress, and applied it to 60 students from Al-Iraqia University, Collge of Education for Women, Department of English. These students were divided into two groups; the control group (30) students, and experimental group (30) students. Both groups were taught the same material, but using different methods.The results of the post-test showed the outperformance of the experimental group over the control group which indicates the good impact of MALL on developing the experimental group’ Pronunciation of word stress